The influence of polycystic ovary syndrome and metabolic syndrome on the choice of the type of delivery: literature review - Yamada, Luciana Shiguemi (2023)
Introduction: Polycystic Ovary Syndrome (PCOS) and Metabolic Syndrome (MS) are interconnected through various physiological pathways, and their coexistence may have significant implications, especially during pregnancy and the childbirth process. During pregnancy, women with PCOS and MS may face an increased risk of obstetric complications. Regarding the impact on childbirth, PCOS and MS can influence the choice of the type of delivery. Methodology: This work constitutes a literature review, following the systematization with the five pillars described below. 1) Problem statement: "What is the influence of PCOS and MS on the choice of the type of delivery?". 2) Relevant studies were identified using the PUBMED platform with the descriptors "Metabolic Syndrome, Polycystic Ovary Syndrome, Parturition, Pregnancy," PUBMED all in accordance with MESH. 3) Initially, 11 studies were selected; 4 were discarded after a thorough reading as they did not contribute to the problem statement. 4) Data extraction was performed using a text editing program. 5) Experts were consulted. Results: The studies revealed that PCOS and MS are associated with a clinically significant increase in the risk of complications during pregnancy compared to control groups. Additionally, there is a 3 to 4 times higher likelihood of developing pregnancy-induced hypertension and preeclampsia, a threefold increase in the risk of gestational diabetes, and a twofold likelihood of premature birth. The elevated obstetric risk for women with PCOS is reflected in a higher rate of spontaneous abortion. Moreover, it was observed that, compared to the general population, PCOS and MS are more associated with cesarean delivery. Conclusion: Cesarean delivery is predominant in patients with PCOS and MS. Furthermore, there is a higher risk of developing pregnancy-induced hypertension, preeclampsia, and premature birth.